Determinant Of Tax Avoidance During Covid-19 Pandemic On Tourism, Restaurant, And Hotel Companies In Indonesia Stock Exchang - Lulu Nailufaroh; Dian Maulita; Dien Sefty Framitha (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
Indonesia's tourism industry occupies the third position in foreign exchange earnings after oil and gas. But the world was shocked by the arrival of the corona virus pandemic in early 2020. Owing to the arrival of this corona virus, the government forced the government to make a new policy, namely Large-Scale Social Restrictions (PSBB). This new policy has had a major impact on the decline in economic progress. Thus,As a result, the revenue of the tourism sector has decreased. Company owners will also usually urge executives to avoid tax by reducing the tax burden. This research plans to examine the elements that have an impact on tax avoidance during the corona virus pandemic in companies that are Indonesia's tourism industry occupies the third position in foreign exchange earnings after oil and gas. But the world was shocked by the arrival of the corona virus pandemic in early 2020. Due to the arrival of this corona virus, the government forced the government to make a new policy, namely Large-Scale Social Restrictions (PSBB). This new policy has had a major impact on the decline in economic progress. Thus income in the tourism sector is reduced. Company owners will also usually urge executives to avoid tax by reducing the tax burden. This research plans to examine the elements that have an impact on tax avoidance during the corona virus pandemic in companies that are included in the classification of the tourism, restaurant, and hotel industries in the first, second, and third quarters of 2020. The research data collected will be processed using regression analysis. multiple. The sampling technique was determined based on the criteria. The results of this research prove that profitability and firm size have a negative effect on tax avoidance. Meanwhile, institutional ownership and audit committee have no effect on tax avoidance. in the classification of the tourism, restaurant, and hotel industries in the first, second, and third quarters of 2020. The research data collected will be processed using regression analysis. multiple. The sampling technique was determined based on the criteria. The results of this research prove that profitability and firm size have a negative effect on tax avoidance. Meanwhile, institutional ownership and audit committee have no effect on tax avoidance.